The handbook of academic writing a fresh approach - Murray, Rowena (Open University Press, 2006)
Aimed at academics, this book offers practical advice. It defines what academic writing is, and the process of getting started through to completion, covering topics such as gaining momentum, reviewing and revising, self-discipline, writing regularly, and writers' groups and retreats.